2017
DOI: 10.1111/jpn.12841
|View full text |Cite
|
Sign up to set email alerts
|

Carcass traits, meat quality, antioxidant status and antioxidant gene expression in muscle and liver of Hu lambs fed perilla seed

Abstract: The effects of perilla (Perilla frutescens L.) seed on carcass traits, meat quality, antioxidant status and antioxidant gene expression in the liver and muscle of Hu lambs were investigated in this study. Sixty Hu lambs (23.02 ± 1.36 kg) were randomly divided into four experimental groups receiving diets containing 0%, 5%, 10% or 15% perilla seed (CD, 5%PFSD, 10%PFSD and 15%PFSD, respectively). The addition of perilla seed had no significant impacts on carcass traits (p > .05). There were no differences in pH,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 37 publications
2
12
1
Order By: Relevance
“…ere were different effects of different antioxidants on SOD. Deng et al [26] added perilla seed (an antioxidant) to longissimus dorsi of lamb and found decreased SOD activity, which was different from the results of our study.…”
Section: Changes Of Superoxide Dismutase (Sod) Activity Andcontrasting
confidence: 99%
“…ere were different effects of different antioxidants on SOD. Deng et al [26] added perilla seed (an antioxidant) to longissimus dorsi of lamb and found decreased SOD activity, which was different from the results of our study.…”
Section: Changes Of Superoxide Dismutase (Sod) Activity Andcontrasting
confidence: 99%
“…Carcass weight and traits are the ultimate indicators of meat-producing animal values. In a recent study, it was shown that carcass traits of Hu lambs were mainly affected by dietary nutrition level [28], rather than weaning ages. As indicated by the similar carcass weight and traits between the two weaning age groups, consistent with the similar live BW, Hu lambs can be weaned at age of 30 without a negative impact on carcass yield or traits.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time PCR was performed according to the protocol described in our previous study [ 35 ] for gene expression quantification. Gen Bank accession numbers and sequences of the corresponding Real-time PCR primer are listed in Table S1 .…”
Section: Methodsmentioning
confidence: 99%